Online Virtual Malaysia Walkthrough (MAWA) (experience the culture) - Amran, Sharib (2009)
Five years ago some of us became familiar with the term 'virtual reality' by reading in computer magazines that soon one will be able to visit cultural heritage sites using a computer. Today, some of the websites display three dimensional (3D) models of objects, buildings and sites so that one can visualise these models from any angle by rotating them on the computer screen. This visualisation is improving and will soon allow the 'virtual visit' of a site, of heritage buildings and of objects surrounding them. This improvement has introduced the term 'virtual tourism' thus providing new tools for heritage site interpretation and presentation, and for sustainable tourism. Online Virtual Malaysia Walkthrough or MAWA is an application that takes Malaysia to the world. Virtual is a representative word for digital or cyber world. MAWA promotes Malaysia in virtual form to attract tourists all over the world to know how Malaysia looks from a far. The tag line is experience the culture. This project would also allow exploring the uses of virtual reality to improve the presentation and interpretation of cultural sites and to extend the carrying capacity of heavily visited sites. The targeted market is the foreign tourists, and the strategy is to attract at least 1% of the total forecasted tourist who will need to pay an access fee of USD20 per entry.